The Development of Chem Man Computer Game as Atomic Constituent Particles Learning Media For 10th Grade High School (UNESA Journal of Chemical Education, 2019)
This study aimed to obtain Chem Man computer game as atomic constituent particles learning media for 10th grade high school. This feasibility was viewed from the validity, practicality, and effectiveness of the game. Method of the research used the Research and Development (R & D) method with three steps, namely (1) preliminary study, (2) development (3) trial. The instruments were used game review sheets, game validity, pre-test and post-test, observation of student activities, students responses, and students interest in learning. The trial was conducted in one class consist of 30 students of X MIPA 7 SMAN 19 Surabaya. The results of content validity and construct validity obtained a percentage in the range between 80% - 93.33% with valid to very valid categories. The practicality in terms of observation of students activities obtained a percentage 98.79% with a very practical category and the response of students gained a percentage 96.67% with a very practical category. The effectiveness in terms of student learning outcomes, namely classical completeness of students got a percentage 100% with a very effective category and the results of participant learning interest questionnaires obtained an overall average percentage 97.78% with high category.Keywords: Chem Man Game, Learning Media, Atomic Constituent Particles